Математичне моделювання розподілу корисних копалин за допомогою поліноміальних інтерлінантів на системі похилих свердловин - Литвин, О.О.; Штепа, Н.І.; Кулик, C.І.; Чорна, О.С. (Проблемы машиностроения, 2014)
Предложен метод моделирования распределения полезных ископаемых при помощи полиномиальных интерлинантов на системе наклонных скважин, размещенных как в одной плоскости, так и произвольным образом. В качестве экспериментальных данных взяты распределение полезных ископаемых в каждой точке системы скважин. Математическая модель позволяет вычислять неизвестное распределение полезных ископаемых между скважинами. Запропонований метод моделювання розподілу корисних копалин за допомогою поліноміальних інтерлінантів на системі похилих свердловин, розміщених як в одній площині, так і довільним чином. Як експериментальні дані взято розподіл корисних копалин в кожній точці системи свердловин. Математична модель дозволяє обчислювати невідомий розподіл корисних копалин між свердловинами. This paper provides an overview of the new minerals distribution mathematical models construction 3D methods by 3 variables functions interlineation methods on a system of inclined boreholes. The problem of constructing minerals distribution spatial mathematical models for the case when the information about minerals distribution function f(x, y, z) is specified in the M inclined boreholes is considered. Methods of three-dimensional mathematical model construction with the use of functions interlineation on an inclined boreholes system, which are based on the use of limited fractionally rational auxiliary functions, are given. The method of minerals distribution modeling with the help of polynomial interlineants on inclined boreholes system placed both in the same plane and in an arbitrary manner is proposed. Experimental data are mineral resources distribution at every point of the boreholes system. The given mathematical model allows calculating an unknown mineral resources distribution between the boreholes.